Complementary Distance and Reciprocal Complementary Distance Spectrum for Indu-Bala Product of Graphs - Ramane, Harishchandra S.; Patil, Daneshwari D. (Sarajevo Journal of Mathematics, 2025)
For two graphs G_1 and G_2, graph obtained with two disjoint copies of join structure G_1 G_2 by joining the corresponding vertices in G_2's, is the Indu–Bala product G_1 G_2. Present work focuses on the study of complementary distance (CD) and reciprocal complementary distance (RCD) spectrum for Indu–Bala product of regular graphs via the concept of equitable partition. Hence note CD and RCD spectrum of dumbbell graph as a particular case of the Indu–Bala product.